Discharging capacity of rectangular side weirs in straight open channels - Emiroglu, M. Emin; Agaccioglu, Hayrullah; Kaya, Nihat (ELSEVIER SCI LTD, 2011)
A side weir is a hydraulic control structure used in irrigation and drainage systems and combined sewer systems. A comprehensive laboratory study, including 843 tests for the discharge coefficient of a sharp-crested rectangular side weir in a straight channel, was conducted in a large physical model under subcritical flow conditions. The discharge coefficient is a function of the upstream Froude number, the ratios of weir length to channel width, weir length to flow depth, and weir height to flow depth. An equation was developed considering all dimensional parameters for discharge coefficient of the sharp-crested rectangular side weir. The average error of the proposed equation is 4.54%. The present study data were compared with ten different discharge coefficient equations developed by several researchers. The study also presents water surface profile and surface velocity streamlines. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Side weir; Water discharge; Discharge coefficient; Intake; Channel flow; Flow measurement; Hydraulic structure; FLOW; COEFFICIENT; Engineering; Instruments & Instrumentation